Vitamin D Deficiency and Vasovagal Syncope in Children and Adolescents - Zhang, Qingyou; Sun, Yan; Zhang, Chunyu; Qi, Jianguang; Du, Junbao (Frontiers in Pediatrics, 2021)
AIMS: To investigate the association of vitamin D deficiency with cardiovascular autonomic nervous system among children and adolescents with vasovagal syncope (VVS). METHODS: This study recruited 76 pediatric patients with VVS and 15 healthy children. The 25-hydroxyvitamin D levels in serum among the participants were evaluated. Heart rate variability analysis including SDNN, rMSSD and SDANN was tested in patients with VVS. The correlation between indices of time-domain analysis and serum vitamin D status of the children with VVS was investigated. RESULTS: In this work, 25-hydroxyvitamin D levels in serum among VVS cases remarkably decreased relative to those among healthy controls (48.76 ± 19.25 nmol/L vs 67.62 ± 15.46 nmol/L, p<0.01). The vitamin D deficient patients with VVS exhibited a lower rMSDD value compared to the non-deficient group with VVS (45.56 ± 16.87 ms vs. 61.90 ± 20.38 ms, p<0.001, respectively). Pearson correlation analysis indicated that serum 25-hydroxyvitamin D levels had positive correlation with rMSDD values (r =0.466, p<0.001). CONCLUSIONS: As suggested by our data, VVS children and adolescents with vitamin D deficiency may have cardiac autonomic dysfunction and cardiac vagal tone decreases with the reduction in vitamine D level.